2022
DOI: 10.1002/1873-3468.14418
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase alleviates autophagic degradation of the endoplasmic reticulum in SPT10‐deficient yeast to enhance triterpene biosynthesis

Abstract: A recent study showed that deletion of the gene encoding the transcription regulator SuPpressor of Ty10 (SPT10) increases total phospholipids, and our previous study established a critical link between phospholipids and the mevalonate/ergosterol (MEV/ERG) pathway, which synthesises triterpenes. This study aims to use spt10Δ yeast to improve triterpene production. Though MEV/ERG pathway was highly expressed in spt10Δ yeast, results showed insufficient accumulation of key metabolites and also revealed massive en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…Moreover, ETC deficiency inhibits autophagy lysosomal hydrolysis either by activating AMPK signaling or by directly activating the lysosomal Ca 2+ channel [ 18 ]. Although previous studies have demonstrated that mitochondria activate the autophagic pathways to alleviate OS in human cells and yeast via Diacylglycerol kinase and All-trans-retinal [ 19 , 20 ], it is unclear which metabolite regulates mitochondrial autophagy under HS in SCs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ETC deficiency inhibits autophagy lysosomal hydrolysis either by activating AMPK signaling or by directly activating the lysosomal Ca 2+ channel [ 18 ]. Although previous studies have demonstrated that mitochondria activate the autophagic pathways to alleviate OS in human cells and yeast via Diacylglycerol kinase and All-trans-retinal [ 19 , 20 ], it is unclear which metabolite regulates mitochondrial autophagy under HS in SCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, dysfunctional mitochondria were associated with decreased ATP synthesis, Ca 2+ imbalance, increased ROS accumulation and lead to oxidative stress (OS) (Ullah et al, 2021). Although mitochondria and ER activate the autophagic pathways to alleviate OS in human cells and yeast via Diacylglycerol kinase and Alltrans-retinal (Ranganathan et al, 2022;Zhang et al, 2020), it is unclear which metabolite regulates mitochondrial and ER induced autophagy under HS in SCs.…”
Section: Introductionmentioning
confidence: 99%